Neurodegeneration Upon Dysfunction of Endosomal/Lysosomal CLC Chloride Transporters - Bose, Shroddha; He, Hailan; Stauber, Tobias (Frontiers in Cell and Developmental Biology, 2021)
The regulation of luminal ion concentrations is critical for the function of, and transport between intracellular organelles. The importance of the acidic pH in the compartments of the endosomal-lysosomal pathway has been well-known for decades. Besides the V-ATPase, which pumps protons into their lumen, a variety of ion transporters and channels is involved in the regulation of the organelles' complex ion homeostasis. Amongst these are the intracellular members of the CLC family, ClC-3 through ClC-7. They localize to distinct but overlapping compartments of the endosomal-lysosomal pathway, partially with tissue-specific expression. Functioning as 2Cl−/H+ exchangers, they can support the vesicular acidification and accumulate luminal Cl−. Mutations in the encoding genes in patients and mouse models underlie severe phenotypes including kidney stones with CLCN5 and osteopetrosis or hypopigmentation with CLCN7. Dysfunction of those intracellular CLCs that are expressed in neurons lead to neuronal defects. Loss of endosomal ClC-3, which heteromerizes with ClC-4, results in neurodegeneration. Mutations in ClC-4 are associated with epileptic encephalopathy and intellectual disability. Mice lacking the late endosomal ClC-6 develop a lysosomal storage disease with reduced pain sensitivity. Human gene variants have been associated with epilepsy, and a gain-of-function mutation causes early-onset neurodegeneration. Dysfunction of the lysosomal ClC-7 leads to a lysosomal storage disease and neurodegeneration in mice and humans. Reduced luminal chloride, as well as altered calcium regulation, has been associated with lysosomal storage diseases in general. This review discusses the properties of endosomal and lysosomal Cl−/H+ exchange by CLCs and how various alterations of ion transport by CLCs impact organellar ion homeostasis and function in neurodegenerative disorders.